Mass Media and the Terror of Terrorism in Global Security Analysis - Ngboawaji Daniel Nte; Irfan Ullah Khan; Onyeka Bienose; Stella Macaulay (Universitas Nusa Cendana, 2020)
Contemporary global security realities have identified the pervasive mass media terror continuum in the form of display of graphic images and somewhat persuasive impacts of the mass media as used by terror organizations across the world. This work is therefore an explorative analytical narrative of the impacts of the mass media in the promotion and consolidation of terrorist ideologies and rationalization of terrorist activities. Generally, the work has made an objective modest attempt to review the nature and dynamics of global mass media and relationship between some of the fallouts of the impacts of the mass media in the spread and sustainability of global extremist and terrorist ideologies. This narrative is derivable from different international scholars and national governments based on sustained empirical researches in different countries of the world. Consequently, this work adopted extensively the historical and explorative approach that relied on secondary sources comprising books, journals and reports that were logically arranged and evaluated through content analysis in tandem with social science research enterprise. The work, therefore, established glaring intrinsic and extrinsic correlation between the impacts of the mass media and terrorism in the world and ultimately offered useful recommendations accordingly to stem this scourge.